Analysis and Research of Key Genes in Gene Expression Network Based on Complex Network. (10th December 2020) - Chen, Guobin; Qi, Jun; Tang, Chao; Wang, Ying; Wu, Yongzhong; Shi, Xiaolong
Abstract : Gene expression network is also a type of complex network. It is challenging to analyze the gene expression network through relevant knowledge and algorithms of a complex network. In this paper, the existing characteristics of genes are analyzed from various indexes of the gene expression network to analyze key genes and TOP genes. Firstly, gene chip data are screened, gene data with obvious characteristics are selected, and relevant clustering characteristics are analyzed. Then, the complex gene network structure is established, and gene networks with different threshold shapes and different sizes are selected. Finally, the relevant indexes and PR values after the PageRank algorithm are analyzed for complex networks under different thresholds, thus establishing the TOP gene and PR sequence.